Re-entrainment in wave-plate mist eliminators - B. J., Azzopardi; K., Sanaullah (Elsevier Science Ltd, 2002)
Wave-plate mist eliminators are among the most e0ective devices to separate liquid from the gas. Liquid separation e3ciency in these devices is largely dependent on the gas super5cial velocity. However, the upper limit of gas throughput is restricted by the re-entrainment of the deposited liquid from the separator surfaces into the gas stream. There is some knowledge available of re-entrainment phenomena in vertical wave-plate separators. This paper presents experiments that have enabled the mechanisms of entrainment to be identi5ed and the boundaries for air and liquid rates at which entrainment starts for horizontal wave-plate separators to be characterised. It is supported by modelling using an extension of earlier work.